Safety and interaction of direct oral anticoagulants with antiarrhythmic drugs - B. A. Tatarsky; N. V. Kazyonnova (Российский кардиологический журнал, 2021)
The use of direct oral anticoagulants minimized the risks associated with vitamin K antagonist (warfarin) therapy. Currently, direct oral anticoagulants have priority over warfarin for the prevention of thromboembolic events in patients with atrial fibrillation and a number of other conditions requiring anticoagulant therapy. Direct oral anticoagulants along with antiarrhythmic therapy are the accepted strategy for atrial fibrillation treatment. At the same time, the effect of drug-drug interactions (DDI) between direct oral anticoagulants and antiarrhythmic drugs, which have common points of metabolic application, has not been fully elucidated. In order to provide effective and safe anticoagulant and antiarrhythmic therapy in patients with AF, it is important to understand the mechanisms and severity of DDI of direct oral anticoagulants and antiarrhythmic agents. This review discusses the issues of DDI of direct oral anticoagulants and antiarrhythmic drugs used to treat atrial fibrillation.